FENOMENA HEALING CULTURE PADA MAHASISWA SEMESTER AKHIR : SYSTEMATIC LITERATURE REVIEW (SLR) - Regina Shafa An Najmah; Mochammad Arista Ferdiansyah; Nursyifa Salsabila Rahmadani Manik; Syalwah Ilmiah Nadifah; Ahmad Fahrezi Fadhil Anam (TARBIYATUL ILMU: JURNAL KAJIAN PENDIDIKAN, 2026)
This research is motivated by the increasing level of academic stress among final-year students who face the demands of completing their thesis, time pressure, and anxiety about the future, which has led to the emergence of healing culture as an alternative strategy for maintaining mental health. This study aims to analyze the phenomenon of healing culture, its role in managing academic stress, and the shift in its meaning among students. The method used is a Systematic literature review (SLR) following PRISMA guidelines, through the search of articles on Google Scholar and Publish or Perish within the 2021–2026 period, with the selection process carried out through identification, screening, and eligibility stages, resulting in 12 relevant articles for analysis. The findings indicate that self-healing serves as an effective emotional regulation strategy in reducing stress, increasing happiness, and strengthening students learning motivation, with practices such as journaling, mindfulness, and self-reflection proven to provide sustainable positive impacts. However, the study also reveals a shift in the meaning of healing into a consumptive lifestyle influenced by social media trends, which has the potential to become an avoidance mechanism for problems. In conclusion, the effectiveness of healing culture largely depends on self-awareness, self-efficacy, and social support, thus requiring a proper understanding to ensure it remains oriented toward mental health and academic achievement.